2001
DOI: 10.1084/jem.194.2.219
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Lymphocyte Function–Associated Antigen (Lfa)-1–Deficient Mice to Determine the Role of Lfa-1, Mac-1, and α4 Integrin in the Inflammatory Response of Neutrophils

Abstract: After injury or infection, neutrophils rapidly migrate from the circulation into tissues by means of an orderly progression of adhesion receptor engagements. Neutrophils have been previously considered to use selectins exclusively to roll on vessels before an adhesion step mediated by the β2 integrins, lymphocyte function–associated antigen (LFA)-1, and Mac-1. Here we use LFA-1−/− mice, function blocking monoclonal antibodies, and intravital microscopy to investigate the roles of LFA-1, Mac-1, and α4 integrins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
3
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(189 citation statements)
references
References 32 publications
8
177
3
1
Order By: Relevance
“…Gamma delta (c d) T cells, which also express high levels of LFA-1, are particularly abundant in the resident lymphocyte population of the liver (47) and have been shown to be important for priming of CD8 + T cells in response to infection (48). In addition, many of the effectors of innate immunity such as neutrophils and macrophages rely on LFA-1 for vascular adhesion and rolling prior to emigration into tissues (49)(50)(51). Such effectors of innate immunity which comprise early inflammatory events can significantly influence T-cell recruitment and acute allograft rejection (52).…”
Section: Discussionmentioning
confidence: 99%
“…Gamma delta (c d) T cells, which also express high levels of LFA-1, are particularly abundant in the resident lymphocyte population of the liver (47) and have been shown to be important for priming of CD8 + T cells in response to infection (48). In addition, many of the effectors of innate immunity such as neutrophils and macrophages rely on LFA-1 for vascular adhesion and rolling prior to emigration into tissues (49)(50)(51). Such effectors of innate immunity which comprise early inflammatory events can significantly influence T-cell recruitment and acute allograft rejection (52).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for other integrins that certain conformational states are likely to be more suited for a transient adhesion like cell spreading, rolling, and migration, whereas other conformations favor a more stable adhesion. For example, it has been demonstrated that the integrin ␣L␤2 can support such a transient adhesion of leukocytes (namely rolling), together with selectins and ␣4 integrins, during inflammation in vivo (52). More recently, this observation could be linked to a certain conformational state of ␣L␤2.…”
Section: Discussionmentioning
confidence: 99%
“…Fully activated LFA-1 mediates the stop of rolling and makes firm adhesion along with Mac-1 (175). Deficiency of b 2 integrin chain causes Leukocyte Adhesion Deficiency Type 1, an inherited disorder that is characterized by inability of leukocytes to undergo adhesion-dependent migration (49).…”
Section: B Integrinsmentioning
confidence: 99%